Construyendo comunidades. Géneros, tiempos, espacios y memorias de los/as bolivianos/as en Ushuaia - Ana Inés Mallimaci Barral (Nuevo mundo - Mundos Nuevos, 2010)
The main objective of this research work that conforms the thesis, is understanding the underlying logics of migrant’s communities construction organized by Bolivians  in Ushuaia city. The assembling of the chosen case interlaces Argentinean’s and Bolivian’s migratory histories, Patagonia’s history and specifically the history of Ushuaia and the way that this last was reconfigured in the austral city. So we are not only talking about the analysis of a migrant group experience but a reflection upon exclusion and inclusion dynamics produced in the national territory by those who are marked as “foreign” adding racial marks that become difficult their acknowledgement as integrants of a national group with their gender and class specificity. So that, one of this research result is the acknowledgment that the path to understand the logics that construct Bolivian sociability as from Ushuaia migrants’ practices necessarily must include the following dimensions: the producer contexts of national and local sense that works as an available whole of limits and resources for the social practices, the mobility experiences present in analysed migratory trajectories that re-configure (far from the classical cannon of what is sedentary) relationships with territories and meanings and senses constructed by the migrants. What is local and what is transnational overlap their effects as a comprehensions frame for the analysed case.